Preliminary evaluation of the treatment of advanced hepatocellular carcinoma with sorafenib - Hiep, Pham Nhu; Quyen, Phan Thi Do; Tuong, Pham Nguyen; Giang, Nguyen Thi Ky; An, Dang Hoang; Phong, Nguyen Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.